Implementasi Agile Project Management pada Proyek TI Sektor Publik: Studi Kasus Direktorat Jenderal Pendidikan Islam - Mutiara Nur Insani Yuwantara; Bob Hardian Syahbuddin (AI Society & STMIK Indonesia, 2025)
The rapid advancement of technology in society has driven government agencies to transform public service delivery through the initiation of information technology (IT) projects. In executing these projects, government institutions must adapt swiftly to changing circumstances. However, the complexity of bureaucratic environments often hinders the adoption of dynamic project management methodologies such as Agile Project Management (APM). This study examines the challenges of implementing APM in IT projects at Indonesia’s Directorate General of Islamic Education (Ditjen Pendis) and identifies strategies to address them. Using a mixed-methods approach (quantitative and qualitative), the research highlights challenges across three dimensions: human resources (HR), processes, and organizational structure. The findings of this study show that the distribution of challenges faced by Ditjen Pendis is dominated by the process category (37%), followed by the HR category (32%) and the organization category (31%). To overcome these, Ditjen Pendis implemented strategies such as fostering open communication, systematizing project documentation, and classifying stakeholders. The results demonstrate that the success of APM in governmental contexts depends not only on technical execution but also on balancing agility with structured bureaucratic governance. The practical implications of this study are expected to guide other government agencies in enhancing their readiness to adopt APM in IT projects, particularly in designing APM-driven digital transformation strategies.